2001
DOI: 10.1021/jo0158534
|View full text |Cite
|
Sign up to set email alerts
|

Direct Reduction of Alcohols:  Highly Chemoselective Reducing System for Secondary or Tertiary Alcohols Using Chlorodiphenylsilane with a Catalytic Amount of Indium Trichloride

Abstract: The direct reduction of alcohols using chlorodiphenylsilane as a hydride source in the presence of a catalytic amount of indium trichloride is described. Benzylic alcohols, secondary alcohols, and tertiary alcohols were effectively reduced to give the corresponding alkanes in high yields. A compound bearing both primary and secondary hydroxyl groups was reduced only at the secondary site to afford the primary alcohol after workup with Bu(4)NF. This system showed high chemoselectivity only for the hydroxyl grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
93
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 188 publications
(96 citation statements)
references
References 14 publications
1
93
0
1
Order By: Relevance
“…It is very surprise to note that the tertiary alcoholic group was reduced in the presence of AC-Ni system. Yasuda et al (2001) reported the catalytic reduction of tertiary alcoholic group into alkane. Based on the literature, it is proposed that the C=C and C-OH group was reduced in the presence of AC-Ni catalyst system.…”
Section: Catalytic Reduction Of A-terpineolmentioning
confidence: 99%
“…It is very surprise to note that the tertiary alcoholic group was reduced in the presence of AC-Ni system. Yasuda et al (2001) reported the catalytic reduction of tertiary alcoholic group into alkane. Based on the literature, it is proposed that the C=C and C-OH group was reduced in the presence of AC-Ni catalyst system.…”
Section: Catalytic Reduction Of A-terpineolmentioning
confidence: 99%
“…Reduction of various alcohols. 16 Additionally, the system was found to give high chemoselectivity for hydroxyl groups in the presence of other functional groups, such as esters, as exemplified by the selective deoxygenation of hydroxy-esters (Scheme 10). Scheme 10.…”
mentioning
confidence: 99%
“…Direct chemoselective reduction of alcohols by Ph 2 SiHCl/InCl 3 . 16 It was proposed that InCl 3 acts as a Lewis acid that loosely coordinates to oxygen to accelerate the deoxygenation of the resulting intermediate by promoting a hydride transfer from silane. 16 While the generation of HInCl 2 was not reported in these earlier studies, the in situ formation of HInCl 2 may also explain the observed reductions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] One of simple and useful methods involves conversion of hydroxy groups to the corresponding alkyl sulfonates, such as tosylates or mesylates, followed by reduction with hydride. As a hydride reagent, LiAlH 4 4 or LiBEt 3 H 5,6 is frequently used for this aim.…”
mentioning
confidence: 99%